Examining the influence of citizen science participation on individual volunteers in the global South: A case study of hydrologic monitors in Veracruz, Mexico. Issue 1 (29th March 2022) - Shinbrot, Xoco A.; Jones, Kelly W.; Solomon, Jennifer; Escobedo, Miriam Ramos
Abstract: Citizen science is increasingly popular for educating and engaging the public, but few studies test how to achieve individual outcomes including knowledge, attitudes, and behaviors, particularly in the Global South. We operationalize the citizen science participation-behavior model for a hydrologic monitoring program in Mexico to evaluate how citizen science participation influences these outcomes. Volunteers were surveyed before, two weeks, and six months after the training, and semi-structured interviews were conducted six months post-training with volunteers and dropouts. While surveys showed that participation had limited impacts on knowledge, retrospective interviews revealed self-described differences in volunteer and dropout environmental identity, self-efficacy, and view of citizen science as a conservation activity. Results show participation spurred volunteers to engage in some activist behaviors. The study provides important evidence concerning the influence of citizen science participation in the Global South on behavioral outcomes and helps inform how to design and implement future citizen science programs. Supplemental data for this article can be accessed online at https://doi.org/10.1080/00958964.2021.1984193 .